2020
DOI: 10.1542/peds.2020-038505b
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Life Support 2020 International Consensus on Cardiopulmonary Resuscitation and Emergency Cardiovascular Care Science With Treatment Recommendations

Abstract: functional outcome at discharge, 30 days, 60 days, 180 days, and/or 1 year; survival only at discharge, 30 days, 60 days, 180 days, and/or 1 year; and ROSC • Study design: RCTs and nonrandomized studies (nonrandomized controlled trials [non-RCTs], interrupted time series, controlled before-and-after studies, cohort studies) eligible for inclusion • Time frame: All languages were included if there was an English abstract. The literature search was updated in September 2019.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 147 publications
1
55
0
10
Order By: Relevance
“…Although animal studies have indicated air is as good as 100% O 2 during this procedure, clinical data are lacking 19 . It is however interesting that the new ILCOR recommendations for paediatric life support phrase this differently: ‘There is insufficient information to recommend a specific inspired oxygen concentration for ventilation during attempted resuscitation after cardiac arrest in infants and children’ 20 . Perhaps the neonatal and paediatric recommendations regarding this issue should be harmonised?…”
Section: Discussionmentioning
confidence: 99%
“…Although animal studies have indicated air is as good as 100% O 2 during this procedure, clinical data are lacking 19 . It is however interesting that the new ILCOR recommendations for paediatric life support phrase this differently: ‘There is insufficient information to recommend a specific inspired oxygen concentration for ventilation during attempted resuscitation after cardiac arrest in infants and children’ 20 . Perhaps the neonatal and paediatric recommendations regarding this issue should be harmonised?…”
Section: Discussionmentioning
confidence: 99%
“…The main finding of higher levels of ECO 2 as a predictor of survival is similar to results from cardiopulmonary resuscitation after the newborn period. 11,12 However, newborns in need of positive pressure ventilation at birth are rarely in cardiac arrest. In a recent study of apnoeic newborns, the first recorded HR was distributed in two peaks around 60 and 165 bpm.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we observed the clinical development and frequently reassessed it, with advanced airway management tools on standby. In the out-of-hospital setting, bag-mask ventilation rather than tracheal intubation or insertion of a supraglottic airway may be recommended [4,8,9]. Indications for intubation or laryngeal mask are respiratory failure or ineffective bag-mask ventilation [4,8].…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to the current guidelines, atropine can be used for bradycardia caused by increased vagal tone or anticholinergic drug toxicity. Epinephrine may be administered to infants and children when bradycardia and poor perfusion are unresponsive to ventilation and oxygenation [8,9]. In the case of poor or absent perfusion, CPR should be started.…”
Section: Literature Reviewmentioning
confidence: 99%